Shysleepyboy
Shysleepyboy
02-12-2015
Mathematics
contestada
Simplify the expression.
3n - 5 + 2n + 4
Respuesta :
masihazerehnazi
masihazerehnazi
02-12-2015
3n
−5
+
2n
+4
=
3n
+
−5
+
2n
+4
Combine Like Terms:
=
3n
+
−5
+
2n
+4
=
(
3n
+
2n
)
+
(
−5
+4
)
=
5n
+
−1
Answer:
=
5n
−
1
Answer Link
VER TODAS LAS RESPUESTAS ( 34+ )
Otras preguntas
D. average amount of annual income earned per person in one year.
Find the quadratic function f(1) =-7 f(3)=-19 and f(3)= -49
It was because she had broken with Billy that Loretta had come visiting to Santa Clara. Billy could not understand. His sister had reported that he had walked
What happens to gravitational potential energy as a roller coaster moves down a hill? It remains constant. It increases. It is converted to kinetic energy. It i
A laboratory technician needs to make a 63-liter batch of a 20% acid solution How can the laboratory technician combine a batch of an acid solution that is pure
Find the area of the figure. Round to the nearest tenth if necessary.
ABCD is a parallelogram. If BC is equal to x + 2 and AD is equal to 12, find x
Which activity was most important to the lives of the Sioux and other Plains Indians?
In a triangle, sides a, b, and c are opposite angles A, B, and C, respectively. If a=15, B=70°, and C=80°, what's the formula for c?
The science of taxonomy has two branches namely------ nd ------